Strategi Guru dalam Pengembangan Logika Anak Usia Dini - Oktani Haloho (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
One type of intelligence that is very important and must be possessed by children is mathematical logic. This study aims to describe effective and efficient strategies that can be implemented by teachers in growing, stimulating and developing mathematical logic intelligence and logical thinking in early childhood at the Pembina Village Kindergarten in Pendahara Village. The method used in this research is descriptive qualitative. The results of the study illustrate that the teacher s strategy in choosing children s learning methods is very important. The development of early childhood logic can be stimulated by learning activities by finding patterns and finding logistical relationships combined with appropriate and fun learning methods.